“OMG It’s not a big deal:” Generation Z’s perceptions of academic integrity and cheating in the 21st century: A phenomenological study - Bernadowski, Carianne (Advances in Social Sciences Research Journal, 2019)
The purpose of this study was to determine Generation Z’s perceptions of cheating in relation to academic integrity, more specifically plagiarism. Utilizing a phenomenological design the researcher identified three key themes, which included social media assistance, helping not cheating, and Google as a learning tool. From these findings, it can be inferred that with the advent of social media and the accessibility of technology, our newest generation enrolled in middle and high school have a relaxed attitude toward academic integrity. The issues that arise from this study provide teachers, administrators and parents reason to pause and question the appropriate use of technology in our connected 21st Century classrooms.